Structured Illumination-Based Super-Resolution Optical Microscopy for Hemato- and Cyto-Pathology Applications - Tieqiao Zhang; Samantha Osborn; Chloe Brandow; Denis Dwyre; Ralph Green; Stephen Lane; Sebastian Wachsmann-Hogiu (Analytical Cellular Pathology)
Structured illumination fluorescence microscopy utilizes interfering light and the moiré effect to enhance spatial resolution to about a half of that of conventional light microscopy, i.e. approximately 90 nm. In addition to the enhancement in the x and y directions, it also allows enhancement of resolution in the z- direction by the same factor of two (to approximately 220 nm), making it a powerful tool for 3-D morphology studies of fluorescently labeled cells or thin tissue sections. In this report, we applied this technique to several types of blood cells that are commonly seen in hematopathology. Compared with standard brightfield and ordinary fluorescence microscopy images, the 3-D morphology results clearly reveal the morphological features of different types of normal blood cells. We have also used this technique to evaluate morphologies of abnormal erythrocytes and compare them with those recorded on normal cells. The results give a very intuitive presentation of morphological structures of erythrocytes with great details. This research illustrates the potential of this technique to be used in hematology and cyto-pathology studies aimed at identifying nanometer-sized features that cannot be distinguished otherwise with conventional optical microscopy.